2011
DOI: 10.1590/s0102-09352011000200031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of piperine in reducing the effects of aflatoxin intoxication in broiler chickens: a preliminary report

Abstract: Communication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…We observed megalocytosis, mononuclear cell infiltrate regions, congestion of epithelial cells of the bile duct, necrosis of biliary ducts, vacuolar degeneration, edema and diffuse vacuolation of hepatocytes. These effects were not found in animals treated with piperine [44]. Cardoso et al [31] evaluated the effect of piperine in different concentrations (60, 120, and 180 mg·kg −1 ) for 35 consecutive days and the best and least toxic concentration was 60 mg·kg −1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed megalocytosis, mononuclear cell infiltrate regions, congestion of epithelial cells of the bile duct, necrosis of biliary ducts, vacuolar degeneration, edema and diffuse vacuolation of hepatocytes. These effects were not found in animals treated with piperine [44]. Cardoso et al [31] evaluated the effect of piperine in different concentrations (60, 120, and 180 mg·kg −1 ) for 35 consecutive days and the best and least toxic concentration was 60 mg·kg −1 .…”
Section: Resultsmentioning
confidence: 99%
“…The aflatoxin was given to broilers which were weighed daily. The doses of piperine and AFB1 used were in accordance with Cardoso et al [31,44]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Dimitri et al 40 reported that exposure to AFB 1 and AFG 2 caused an average of 539 g (16%) body weight loss in rabbits, and this was related to impaired protein synthesis and DNA synthesis. Cardoso et al 41 stated that the mixture containing 62.9% of AFB 1 and 37.1% of AFG 1 significantly decreased the body weight gain in broiler chicks, did not cause a change in liver anatomy in terms of shape, texture and color, however, it caused an increase in relative liver weight.…”
Section: Resultsmentioning
confidence: 99%
“…The aflatoxins B 1 , B 2 , G 1 and G 2 produced by Aspergillus flavus and A. parasiticus are considered the most relevant group in Brazil due to their high incidence and the toxic effects they have on humans and animals (Arana et al 2011;Cardoso et al 2011;Hoeltz et al 2012). When ingested by an animal, AFB 1 is biotransformed in the liver and excreted in the milk as AFM 1 (Hussein and Brasel 2001).…”
Section: Introductionmentioning
confidence: 99%